Female mice are more prone to develop an addictive-like phenotype for sugar consumption - Wei, Shoupeng; Hertle, Sarah; Spanagel, Rainer; Bilbao, Ainhoa (Scientific reports, 2021)
The concept of “sugar addiction” is gaining increasing attention in both the lay media and scientific literature. However, the concept of sugar addiction is controversial and only a few studies to date have attempted to determine the “addictive” properties of sugar using rigorous scientific criteria. Here we set out to systematically test the addictive properties of sugar in male and female mice using established paradigms and models from the drug addiction field. Male and female C57BL/6N (8-10 weeks old) were evaluated in 4 experimental procedures to study the addictive properties of sugar: (i) a drinking in the dark (DID) procedure to model sugar binging; (ii) a long-term free choice home cage drinking procedure measuring the sugar deprivation effect (SDE) following an abstinence phase; (iii) a long-term operant sugar self-administration with persistence, motivation and compulsivity measures and (iv) intracranial self-stimulation (ICSS). Female mice were more vulnerable to the addictive properties of sugar than male mice, showing higher binge and long-term, excessive drinking, a more pronounced relapse-like drinking following deprivation, and higher persistence and motivation for sugar. No sex differences were seen in a compulsivity test or reward sensitivity measured using ICSS following extended sugar consumption. This study demonstrates the occurrence of an addictive-like phenotype for sugar in male and female mice, similar to drugs of abuse, and suggests sex-dependent differences in the development of sugar addiction.